The Authority and Duties of the People's Consultative Assembly (MPR) as a High State Institution of the Republic of Indonesia - Beni Suswanto; Irabiah; Muh. As Ari AM (Journal of Creative Power and Ambition (JCPA), 2026)
Along with the development of reform, democracy and the Indonesian state system, the position and authority as well as the duties of the People's Consultative Assembly (MPR) have changed. The change is quite significant, previously the position of the MPR as the highest state institution of the Republic of Indonesia, which then the position of the MPR became equal to other high state institutions. This study aims to determine the Authority and Duties of the People's Consultative Assembly (MPR) as a High State Institution of the Republic of Indonesia. This study uses a Normative Juridical research approach. The results of the study regarding the Authority and Duties of the People's Consultative Assembly (MPR) as a High State Institution of the Republic of Indonesia, namely: The People's Consultative Assembly has the authority to amend and stipulate the Constitution, the People's Consultative Assembly inaugurates the President and/or Vice President and the People's Consultative Assembly can only dismiss the President and/or Vice President during their term of office in accordance with the Constitution. Furthermore, the authority and duties of the People's Consultative Assembly (MPR) as regulated in Article 8 paragraph (2) and paragraph (3) of the 1945 Constitution, are further regulated in Article 4 and Article 5 of the Republic of Indonesia Law Number 17 of 2014 concerning the People's Consultative Assembly, the People's Representative Council, the Regional Representative Council, and the Regional People's Representative Council. Law No. 17 of 2014 specifically regulates the scope of the MPR's powers.